1943
DOI: 10.1017/s0007485300023464
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Siricidae, especially of Europe and southern Asia (Hymenoptera, Symphyta)

Abstract: 1. These studies were originally intended to form the basis of a world monograph of the Siricidae ; such a work cannot be completed under present circumstances.2. Two ratios are introduced as useful characters for separating species : the ovipositor/forewing ratio and the sawsheath/ovipositor ratio. These ratios were obtained from all specimens of all the species represented in the British Museum collections and the results are tabulated. They were found not to vary with the size of the insects.The former rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…Sirex noctilio and its symbiotic fungal associate, Amylostereum areolatum , are indigenous in the temperate regions of the Northern Hemisphere and are thought to be of Eurasian origin (Benson, 1943; Morgan, 1968; Spradbery & Kirk, 1978). In these regions, this insect–fungus complex is considered a secondary problem of little economic importance (Chrystal, 1928; Hanson, 1939; Hall, 1978; Spradbery & Kirk, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Sirex noctilio and its symbiotic fungal associate, Amylostereum areolatum , are indigenous in the temperate regions of the Northern Hemisphere and are thought to be of Eurasian origin (Benson, 1943; Morgan, 1968; Spradbery & Kirk, 1978). In these regions, this insect–fungus complex is considered a secondary problem of little economic importance (Chrystal, 1928; Hanson, 1939; Hall, 1978; Spradbery & Kirk, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In return, the fungi provide a suitable environment, nutrients, and enzymes that are necessary for the survival and development of the insect larvae (Slippers et al 2003). In general, the woodwasps spend most of their life as burrowing larvae in host trees while adult wasps live only for a few weeks to mate and lay eggs in other trees every one to three years (Benson 1943; Morgan 1968). This type of insect–fungal complex does not usually result in obvious economic and ecological damage.…”
Section: Macrofungi In Mutualistic Relationships With Animalsmentioning
confidence: 99%
“…Both genera share the loss of cerci in female, but Afrotremex has a shorter fore wing cell 2R1 relative to cell 3R1. Benson (1943), while maintaining T. hyalinatus as part of Tremex, suggested that it should be put in its own genus. Pasteels (1951) agreed and proposed Afrotremex to include T. hyalinatus and added a new species, A. violaceus, for the same reasons brought up by Benson.…”
mentioning
confidence: 99%